Rap1 Activity Is Essential for Focal Adhesion and Slit Diaphragm Integrity - Maywald, Mee-Ling; Picciotto, Cara; Lepa, Carolin; Bertgen, Luisa; Yousaf, Farwah Sanam; Ricker, Andrea; Klingauf, Jürgen; Krahn, Michael P.; Pavenstädt, Hermann; George, Britta (Frontiers in Cell and Developmental Biology, 2022)
Glomerular podocytes build with their intercellular junctions part of the kidney filter. The podocyte cell adhesion protein Nephrin is essential for developing and maintaining slit-diaphragms as functional loss in humans results in heavy proteinuria. Nephrin expression and function is also altered in many adult-onset glomerulopathies. Nephrin signals from the slit-diaphragm to the Actin cytoskeleton and Integrin β1 at focal adhesions by recruiting Crk family proteins, which can interact with the Rap guanine nucleotide exchange factor 1 C3G. As Rap1 activity affects focal adhesion formation, we hypothesize that Nephrin signals via Rap1 to Integrin β. To address this, we combined Drosophila in vivo and mammalian cell culture experiments. We find that Rap1 is necessary for correct targeting of Integrin β to focal adhesions in Drosophila nephrocytes, which also form slit-diaphragm-like structures. In the fly, Rap1 activity is important for signaling of the Nephrin ortholog to Integrin β, as well as for Nephrin-dependent slit-diaphragm integrity. We show by genetic interaction experiments that Rap1 functions down-stream of Nephrin signaling to Integrin β as well as down-stream of Nephrin signaling necessary for slit-diaphragm integrity. Similarly, in human podocyte culture Nephrin activation results in increased activation of Rap1. Thus, Rap1 is necessary for down-stream signal transduction of Nephrin to Integrin β.